Prediction of Educational Achievement Based on Learning Styles Mediated by Academic Self-Efficacy: A Case Study on the Students of Medical Professionals in Kerman University of Medical Sciences, Iran - Hossein Motahhari; Mahdi Lesani; Hamideh Jahangard (Kerman University of Medical Sciences, 2017)
Background and Objectives Studying the factors affecting educational achievement is complicated as educational achievement is a multidimensional element and is delicately associated with physical, social, cognitive, and emotional growth of students. The current study aimed to predict educational achievements of students of medical professionals in Kerman University of Medical Sciences, Kerman, Iran, based on learning styles and mediation by educational self-efficacy. Methods The current correlational study was conducted cross-sectionally. The study population included all students of medical professionals in Kerman University of Medical Sciences, and, using Cochran's formula, a total of 286 participants were selected by stratified random sampling. The Kolb learning style inventory and McIlroy and Bunting academic self-efficacy scale were used as data gathering tools. Current grade point average (GPA) was used to measure academic achievement. Data were analyzed using structural equations and model fitting indices in AMOS software. Results According to the results of the current study, there was a structural relationship between the learning styles mediated by academic self-efficacy and academic achievements. Additionally, results of the current study indicated the fitness of the model in the study population. Conclusions Results of the current study indicated the positive effect of different learning styles on academic achievements of students and that different learning styles can be employed to train students. On the other hand, the mediating role of academic achievements of students can enhance their academic achievements. By such methods, teachers can benefit from different educational strategies, and active learning occurs.